LUPUS VULGARIS DENGAN LESI DISEMINATA - Jayadi, Nana N.; Ernaningtyas, Niken; Niode, Nurdjannah J.; Wongkar, Marthen C. P. (UNIVERSITAS SAM RATULANGI, 2015)
Abstract: Lupus vulgaris (LV) is a chronic progressive form of paucibacillary cutaneous tuberculosis. Lesion is usually solitary in the form of nodes or erythematous plaques with an apple-jelly sign on diascopy. Disseminated LV is a rare form of cutanoeus tuberculosis with multiple lesions in several body areas. We reported a male of 40 years old with a suppurative wound on the left neck and reddish nodules on the face, neck, trunk, and limbs along with fever, night sweats, weight loss, and history of previous TB infections. There were multiple erythematous nodules and painful suppurating ulcers with enlargement of several lymph nodes. Apple-jelly sign appeared on diascopy. The FNAB showed specific granulamatous inflammation for TB with lymphocytes, epitheloid macrophages, and multinucleated giant cells. The histopathological finding showed tubercles surrounded by macrophages and lymphocytes. Anti-tuberculosis drugs category I were given for 6 months, ofloxacin, and open wound care compressed with NaCl 0.9%. In the third month of observation, there was significant improvement. Conclusion: This case was diagnosed as lupus vulgaris based on the history of lymphadenitis TB and scrofuloderma, lesions in several body area with positive diascopy test, the FNAB as well as the histopathologic result supporting the diagnosis of tuberculosis, and there was significant improvement after treatment with antiTB drugs.Keywords: lupus vulgaris, diseminata, tuberculosis, ofloksasinAbstrak: Lupus vulgaris (LV) merupakan tuberkulosis (TB) kutis pausibasiler kronis dan progresif. Lesi biasanya soliter, berupa nodus atau plak eritematosa dengan gambaran apple-jelly pada diaskopi. Lupus vulgaris diseminata merupakan bentuk TB kutis yang jarang ditemukan dengan lesi multipel pada beberapa area tubuh secara bersamaan. Kami melaporkan seorang laki-laki, 40 tahun, dengan luka bernanah pada leher kiri dan benjolan-benjolan kemerahan pada wajah, leher, badan, dan tungkai disertai demam, keringat malam, penurunan berat badan dan riwayat infeksi tuberkulosis sebelumnya. Pada pemeriksaan fisik tampak nodus eritematosa multipel disertai ulkus bernanah dan pembesaran beberapa kelenjar getah bening. Gambaran apple-jelly tampak pada diaskopi. Pemeriksaan FNAB menunjukkan gambaran radang granulomatik spesifik TB dengan adanya sel-sel radang limfosit, kelompok makrofag epiteloid, dan sel-sel datia Langhans. Pemeriksaan histopatologis memberikan gambaran tuberkel yang dikelilingi oleh makrofag dan limfosit. Terapi diberikan berupa OAT kategori I selama 6 bulan, ofloksasin, dan kompres terbuka dengan NaCL 0,9%. Pada bulan ketiga tampak perbaikan signifikan. Simpulan: Pada kasus ini, diagnosis lupus vulgaris ditegakkan berdasarkan adanya riwayat limfadenitis TB dan skrofuloderma, lesi di beberapa area tubuh sekaligus dengan pemeriksaan diaskopi positif, gambaran FNAB dan histopatologis menunjang diagnosis TB, dan pengobatan dengan OAT memberikan perbaikan bermakna.Kata kunci: lupus vulgaris, diseminata, OAT, ofloksasin